The political sociology of cosmopolitanism and communitarianism representative claims analysis - De Wilde, Pieter 1980-; Koopmans, Ruud 1961-; Zürn, Michael 1959- (WZB, 2014)
This WZB Discussion Paper documents in detail the representative claims analysis conducted within the WZB bridging project 'The Political Sociology of Cosmopolitanism and Communitarianism'. It serves as methodological background for interpreting the dataset and findings based upon it. The paper includes the aims of this empirical mod-ule in relation to the project, the sampling strategy, the codebook with descriptive statistics from the database, and the results of the intercoder reliability test. The annexes include examples of coded claims and a guide to the database, both in its more qualitative and in its fully quantitative forms.
Zsfassung in dt. Sprache